2009
DOI: 10.1177/193229680900300627
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic-Directed Vesicle Insulin: A Review of Formulation Development and Preclinical Evaluation

Abstract: Hepatic-directed vesicle insulin (HDV-I), a novel investigational vesicle (<150 nm diameter) insulin delivery system that carries insulin and a specific hepatocyte-targeting molecule (HTM) in its phospholipid bilayer and has the ability to mimic a portal vein insulin infusion remotely [subcutaneous (SC) HDV-I] and noninvasively (oral HDV-I), has been developed. This review summarizes formulation development, subsequent refinements, and results of preclinical evaluation studies, including biodistribution, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…The vesicles contain a specific proprietary hepatocyte-targeting molecule -biotinphosphatidylethanolamine -in their phospholipid bilayer. Clinical trials in adult patients with type 1 diabetes mellitus demonstrated that the postprandial glycaemic control produced by 0.1 and 0.2 U/kg oral HDV-I was similar to that produced by 0.07 U/kg SC Humulin R [7].…”
Section: Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The vesicles contain a specific proprietary hepatocyte-targeting molecule -biotinphosphatidylethanolamine -in their phospholipid bilayer. Clinical trials in adult patients with type 1 diabetes mellitus demonstrated that the postprandial glycaemic control produced by 0.1 and 0.2 U/kg oral HDV-I was similar to that produced by 0.07 U/kg SC Humulin R [7].…”
Section: Liposomesmentioning
confidence: 99%
“…All these effects are due to the fact that oral route provide insulin directly to the liver through portal circulation, resembling that which occurs in the non-diabetic individual [6]. The achievement of an adequate level of insulin in portal circulation has been associated with more a rapid and significant lowering of plasma glucose and haemoglobin A1c levels, the normalization of the plasma levels of three carbon precursors -such as lactate, pyruvate and alanine -and the hormones cortisol, growth hormone and glucagon [7].…”
Section: Oral Delivery Of Insulin: Why?mentioning
confidence: 99%
“…Still, the vast majority of HDV-I was the free form encapsulated inside of vesicles (99% free INS). 25 In addition, vesicles with increased diameter over 90 nm exhibit increased uptake by nonparenchymal cells which decreases the specificity to hepatocytes. 26 The final example of active liver targeting is Proinsulin-transferrin (ProINS-Tf) fusion protein, which consists of the inactive human INS precursor, ProINS, and Tf.…”
Section: Current Strategies In Liver Targeted Insulin Deliverymentioning
confidence: 99%
“…INS is then dissociated from the lipid complex over time and exerts INS action in the liver. 24,25 HTM is composed of molecules targeted either the asialoglycoprotein (galactose) receptor, hepatobiliary receptor or biotin receptor on hepatocytes. The amount of INS delivered to liver has been enhanced in the HDV-I formulation.…”
Section: Current Strategies In Liver Targeted Insulin Deliverymentioning
confidence: 99%
“…Hepatic targeted insulin has been demonstrated to significantly reduce the postmeal hyperglycemic area under the curve (AUC) by using oral glucose tolerance tests (OGTTs) in dogs (5). Postmeal blood glucose AUCs in dogs are elevated after pancreatectomy due to insulin deficiency, but blood glucose AUCs are not normalized after pancreatectomy when treated with replacement SC insulin.…”
mentioning
confidence: 99%